An Analysis of the Mediational Effect of Socio-Cultural Factors on Student's Career Choice Outcomes in the Built Environment: Applying the Socio-Cognitive Career Theory - Mariam Akinlolu; Temitope Omotayo; Obas John Ebohon; Damilola Ekundayo (MDPI AG, 2023)
Investigations into career development revealed the significant influence of social and cultural determinants, notably familial factors, on children's professional aspirations. Such aspirations are moulded by their milieu, individual interests, academic environments, and socio-economic contexts. South Africa's unique socio-political history introduces complexity into career development pathways. The intricate relationships between ethnicity, gender, and socio-economic backgrounds vis-a-vis career outcomes of South African youth remain underexplored. This research aimed to understand these influences within the construction domain, emphasising cognitive facets such as self-efficacy and societal endorsements. The Social Cognitive Career Theory (SCCT) served as the foundational framework, with structural equation modelling employed for causal analysis. A focus was given to early university students, predominantly from Construction Management. The study showcased pathways for informed career decisions in construction and underscored the relevance of the SCCT, especially for women in traditionally male-dominated sectors. The study culminated in unveiling pathways for informed career decisions in construction, reinforcing the pertinence of the SCCT framework, especially concerning women in traditionally male-dominated spheres like construction. Acknowledging the scarcity of empirical studies using SCCT within the construction sphere is pertinent.